A Discourse Analysis on the Performance of ‘Feminine Energy’ Narratives on Tiktok - Octavia, Ocha; Gultom, Mita Setriana; Audrey, Nazzaura Kayla; Ginting, Teza Aditra; Silalahi, Kevindo; Putri, Dian Marisha (Journal of English Language and Education, 2026)
The idea of “feminine energy” has become popular on TikTok, where many women share videos encouraging others to be calm, gentle, and soft as a way to feel empowered. These videos often use soft voices, elegant visuals, and positive language to promote what they call “true femininity.” However, this kind of content can also bring back old gender stereotypes that expect women to be passive and polite. This study explores how the idea of “feminine energy” is shown through language and behavior on TikTok, how audiences react to it, and what it means for women’s empowerment. Using Robin Lakoff’s Language and Woman’s Place (1975) and Fairclough’s Discourse Theory (1992), this research analyzes 10 TikTok videos under the hashtags #FeminineEnergy, #Feminine, and #WomanPower. The findings show that while many women see the “feminine energy” trend as self-improvement, the language and visuals often repeat traditional gender roles. The study concludes that the trend presents femininity as empowerment, but still within the limits of old social expectations.